2D bio-based nanomaterial as a green route to amplify the formation of hydrate phases of cement composites: Atomistic simulations and analytical characterization. (13th September 2021) - Chi, Yin; Huang, Bo; Saafi, Mohamed; Fullwood, Nigel; Lambert, Colin; Whale, Eric; Hepworth, David; Ye, Jianqiao
Highlights: Novel 2D CNS reinforcing material synthesized sugar beet waste. MD and DFT simulations investigated the effect of CNS on hydration. MD and DFT uncovered new positive effects of CNS on hydration. The CNS amplified the hydration of cement. A hydration mechanism for the new cementitious composites is proposed. Abstract: Ordinary Portland cement (OPC) is the binding element in concrete materials and, CO2 emissions associated with its manufacturing and use is about 8% of the world's CO2 emissions. The engineering properties of hardened concrete depend on the amount of the hydrate phases in OPC. If the growth of the hydrate phases could be increased, the performance of concrete would be significantly improved, and the consumption of OPC will be decreased, and its environmental footprint will be reduced. In this paper, we present a new green approach for controlling the growth of the hydrate phases in OPC using bio flakes composed of staked carrot-based two-dimensional (2D) nanosheets (CNSs) synthesized from carrot waste. Density-functional theory and reactive molecular dynamics (DFT-MD) simulations were carried out in conjunction with analytical characterization to examine the interfacial interaction between CNS with tricalcium silicate Ca3 SiO5 (C3 S), the main constituent of OPC and understand how they influence the growth of the hydrate phases in OPC. The DFT-MD simulations results show the 2D CNS dissolves due to its interfacial interaction with the highly reactive C3 S, leading to a series of fast proton exchange in C3 S. This in return accelerates the dissolution rate of C3 S thereby amplifying the growth of the hydrate phases. The DFT-MD simulations also show that the dissolution of the 2D CNS creates new several organic compounds that enhance the mobility and dynamics of protons that further amplify the dissolution rate of C3 S. The analytical results from scanning electron microscope (SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), and thermography analysis (TGA) and differential scanning calorimetry (DSC) show a significant growth of the hydrate products in OPC due to interfacial dissolution of C3 S and some CNS thus, confirming the DFT-MD results. This work demonstrates that the growth of the hydrate products in OPC can be amplified by the addition of green and renewable 2D bio-based nanomaterials. This green approach provides a base for the design and development of low-carbon cementitious materials.